1974
DOI: 10.1002/pssa.2210220242
|View full text |Cite
|
Sign up to set email alerts
|

Temperature dependence and activation parameters of creep in Zn in the temperature range 1.5 to 80 °K

Abstract: Data necessary to determine the activation energy and volume of the creep process in zinc have been obtained in the temperature range 1.5 to 80 °K by means of a differential technique. While calculating the activation parameters the influence of quantum phenomena on fluctuation‐induced dislocation motion over local barriers of the crystal lattice were taken into account. The analysis of the dependences of the activation parameters on temperature and effective stress shows that below a certain characteristic te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

1977
1977
2018
2018

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…Early proponents included [20,24,26,27]. Conversely, subsequent work by [13,22,23] suggests that, even to 4 K, creep is time-dependent and is a result of the thermal activation of dislocations.…”
Section: Discussion Of the Mechanisms Of Low-temperature Creep Logarimentioning
confidence: 91%
See 2 more Smart Citations
“…Early proponents included [20,24,26,27]. Conversely, subsequent work by [13,22,23] suggests that, even to 4 K, creep is time-dependent and is a result of the thermal activation of dislocations.…”
Section: Discussion Of the Mechanisms Of Low-temperature Creep Logarimentioning
confidence: 91%
“…Seeger et al [19,33,34] proposed a dislocation intersection mechanism for pure FCC metals under polyslip. Others have suggested that creep occurs due to quantum mechanical tunneling of dislocations at very low temperature [13,20,22,24,26,27], but there is no consensus as to the actual mechanisms involved.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…Exceptional reviews of the widespread studies on the topic may be found in some important references [80][81][82]. Also, some studies were done regarding the proposition of quantum mechanical tunneling of dislocations at very low temperature [83][84][85][86][87][88].…”
Section: Creep 200mentioning
confidence: 99%
“…NATSIK et al (1972; 1979) proposed a theory in which the zero-point vibration of dislocation segments influences the surmounting process of the dislocation over a point barrier, and explained anomalous creep behaviour of various metals a t helium temperatures which was reported by the school of STARTSEV (NATSIK et al 1972;OSETSKII et al;1974a, b ;KOVAL et al). The inertial effect (GRANATO; SUENAGA et al) and the zipper effect (LANDAU 1973(LANDAU , 1975 have also been considered to be responsible for the low temperature anomaly of soft metals.…”
Section: Introductionmentioning
confidence: 94%